2015
DOI: 10.1111/ajt.13144
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Deceased Donor Kidney Injury With Kidney Discard and Function After Transplantation

Abstract: Deceased-donor kidneys with acute kidney injury (AKI) are often discarded due to fear of poor outcomes. We performed a multicenter study to determine associations of AKI (increasing admission-to-terminal serum creatinine by AKI Network stages) with kidney discard, delayed graft function (DGF) and 6-month estimated glomerular filtration rate (eGFR). In 1632 donors, kidney discard risk increased for AKI stages 1, 2 and 3 (compared to no AKI) with adjusted relative risks of 1.28 (1.08–1.52), 1.82 (1.45–2.30) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
183
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(198 citation statements)
references
References 33 publications
(24 reference statements)
9
183
2
1
Order By: Relevance
“…However, consistent with work by our group and others, we find only minor adverse effects of donor AKI on posttransplant recipient outcomes. 33,34 This study provides additional evidence that transplantation using deceased-donor kidneys with AKI often leads to good allograft function and that transplant centers should consider acceptance of these kidneys. On the other hand, the development of better tools to profile donor kidney quality and extend the survival of transplanted kidneys remains a high priority for the field of transplantation.…”
Section: Discussionmentioning
confidence: 76%
“…However, consistent with work by our group and others, we find only minor adverse effects of donor AKI on posttransplant recipient outcomes. 33,34 This study provides additional evidence that transplantation using deceased-donor kidneys with AKI often leads to good allograft function and that transplant centers should consider acceptance of these kidneys. On the other hand, the development of better tools to profile donor kidney quality and extend the survival of transplanted kidneys remains a high priority for the field of transplantation.…”
Section: Discussionmentioning
confidence: 76%
“…Mean serum creatinine concentration was 2.41 ± 0.88 mg/dL at time of procurement and 1.06 ± 0.32 mg/dL on admission in AKI donors, and 0.81 ± 0.26 mg/dL in controls (Table 1). AKI donors had a lower 24-h urine production (3.22 ± 1.95 vs. 4.59 ± 2.53 L, p = 0.009), were more frequently exposed [13][14][15][16][17][18][19][20][21][22][23] days in controls, p = 0.05) ( Table 3). While significant elevations in serum creatinine were noted in these patients until 10 days after transplantation, this difference lost statistical significance by day 14 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Outcome was not different in the three strata with regard to patient/graft survival, and renal function [12]. Unexpectedly, the well-known adverse effect of delayed graft function (DGF) on graft survival could not be seen in recipients of AKI kidneys, but was evident in recipients of standard donor kidneys [12,18]. Klein et al [13] reported their extensive center experience in a study of 1518 renal transplant recipients between 1998 and 2008, including 485 transplants from a DBD with AKI (defined by a donor serum creatinine concentration >1.5 mg/dL).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…14,15 Briefly, we collaborated with five organ procurement organizations (OPOs). These OPOs collected donor urine samples as per study protocol at the time of organ procurement between April 2010 and November 2013 from donors whose surrogates had given consent for research.…”
Section: Methodsmentioning
confidence: 99%